Enhancing Personalized Learning Using Artificial Intelligence and Machine Learning Approaches - Shaumiwaty, Shaumiwaty; Mochamad Heru Riza Chakim; Heni Nurhaeni; Victorianda (Blockchain Frontier Technology, 2025)
The convergence of artificial intelligence (AI) and machine learning (ML) technologies has revolutionized the education landscape, shifting paradigms toward individualized and optimized learning environments. By harnessing AI predictive power and ML adaptive capabilities, educational outcomes are enhanced while equipping teachers with data driven insights for informed decision making. The primary objective of this research is to explore how customized learning environments, ML models, performance measurement, and AI algorithms improve educational outcomes and learning experiences. Despite the rapid advancements in AI driven education, a gap exists in the integration of AI powered personalization with statistical validation techniques like SmartPLS, particularly in evaluating its direct impact on student engagement and performance. The novelty of this study lies in its emphasis on AI driven customization in learning, utilizing advanced statistical validation techniques to provide empirical support for personalized education models. The method involves a survey based approach combined with SmartPLS statistical modeling to analyze correlations between AI driven learning adaptations and educational outcomes. The findings from the result and discussion indicate a positive impact of AI algorithms and ML models on academic success, individualized learning, and improved performance measures, with most hypotheses yielding significant results. These insights align with emerging trends in personalized and adaptable learning and technological advancements, such as immersive experiences and the integration of virtual reality. By addressing the research gap and validating AI driven learning models through SmartPLS, this study contributes to the growing body of knowledge in AI enhanced education, demonstrating the effectiveness of intelligent, data-driven learning environments in fostering better academic performance and engagement.